Effects of the 2007–2009 financial crisis on mergers and acquisitions in the United States. - Ng, Mark Seng Lee. (2011)
We examine a sample of 255 domestic acquisitions by publicly listed companies in the United States during the financial crisis of 2007 – 2009. We study two aspects of corporate acquisitions during the crisis environment of 2007 - 2009, namely the probability of deals being successfully completed and acquirer shareholder returns following deal announcements. For deal success, we find larger acquirers and acquirers which finance acquisitions entirely in cash to have a greater probability of completing the transaction. As for abnormal returns, we find acquirers with greater leverage and acquirers which finance acquisitions entirely in cash to have greater abnormal returns. To our expectation, we also found acquirer size to not be a significant variable in determining abnormal returns. Our findings are also consistent with the debt-monitoring and information asymmetry hypotheses established in earlier theoretical literature.